The Role of Blue Technology as a Driver in Realizing Sustainable Production of People’s Salt in East Java Province - Badi'ah, Roudlotul; Wiratama, Dadang; Indira, Irma; Aprilia Rahma, Arsa; Fanani, Fahmi (Graduate Program Magister Manajemen Pendidikan, 2024)
This study explores how institutions and knowledge management influence the success of blue technology adoption in supporting sustainable community salt production in East Java Province. This research employs a quantitative approach, with primary data gathered through questionnaires distributed to salt farmers across various regencies/cities in East Java Province. The data was analyzed using structural equation modeling-partial least squares (SEM-PLS) with the assistance of SmartPLS 4 software to address the study’s objectives. The study results indicate that institutions positively influence sustainable production, with blue technology as a significant mediator in the relationship. In addition, knowledge management has also been proven to have a positive effect on sustainable production, where blue technology again significantly mediates this relationship. Overall, blue technology has a positive impact on the sustainability of salt production in East Java Province. This study offers novelty by highlighting the role of blue technology as a mediator in the relationship between institutions and knowledge management with sustainable production. In addition, this study emphasizes the importance of blue technology in increasing efficiency, reducing environmental impacts, and strengthening the adoption of innovative production method technology, waste management, salt processing products, and the use of renewable energy in more environmentally friendly salt businesses, which have not been widely discussed before.